Early fossils illuminate character evolution and interrelationships of Lampridiformes (Teleostei, Acanthomorpha). (2nd September 2014) - Davesne, Donald; Friedman, Matt; Barriel, Véronique; Lecointre, Guillaume; Janvier, Philippe; Gallut, Cyril; Otero, Olga
<x xml:space="preserve">Abstract</x> Lampridiformes is a peculiar clade of pelagic marine acanthomorph (spiny‐rayed) teleosts. Its phylogenetic position remains ambiguous, and varies depending on the type of data (morphological or molecular) used to infer interrelationships. Because the extreme morphological specializations of lampridiforms may have overwritten the ancestral features of the group with a bearing on its relationships, the inclusion of fossils that exhibit primitive character state combinations for the group as a whole is vital in establishing its phylogenetic position. Therefore, we present an osteological data set of extant (ten taxa) and fossil (14 taxa) acanthomorphs, including early Late Cretaceous taxa for which a close relationship with extant Lampridiformes has been suggested: †Aipichthyoidea, †Pharmacichthyidae, and †Pycnosteroididae. We find that all three taxa plus Lampridiformes form a clade that we call Lampridomorpha. Under this hypothesis, †Aipichthyoidea is paraphyletic. The inclusion of fossils in the analysis changes the topology, highlighting their critical importance in phylogenetic studies of morphological characters. When fossils are included, Lampridomorpha is sister to Euacanthomorpha (all other extant acanthomorphs), concurring with most previous anatomical studies, but conflicting with most molecular results. Lampridomorpha as a whole was a major component of the earliest acanthomorph faunas, notably in the Cenomanian. © 2014 The Linnean Society of London